Early development of Barbel (Barbus barbus L.) larvae - Çalta, Metin (My University, 1998)
In this study, the early development of barbel (Barbus barbus L.) larvae has been determined by measuring their wet weight, dry weight, whole body mineral content (Ca, Mg, Na and K), skeletal development and gill development. It has been observed that wet weight, whole body mineral contents, the number of lamellae per filament of gill and the number of calcified vertebrae of larvae during early development stage increased by age, whereas dry weight decreased. The increase of whole body magnesium content has been very low compared with that of other minerals. In addition, a possitive relationship between whole body calcium content and the number of calcified vertebrae has been found.
Keywords: Barbus barbus L.; Dry weight; Gill development; Skeletal development; Wet weight; Whole body mineral content